P77 Experience of a joint palliative and respiratory clinic on niv treatment initiation in motor neurone disease. (15th November 2016) - Burden, T; Davis, C; Johnstone, E; Spence, J; Shrikrishna, D
Abstract : Introduction: Signs and symptoms of ventilatory failure are a proxy for disease progression in Motor Neurone Disease (MND). Recent National Institute for Health and Clinical Excellence (NICE) guidance for MND recommends early referral to specialist palliative care (NICE, 2016) and this may help inform patient decisions around the initiation of non-invasive ventilation (NIV) A service evaluation was conducted on a new joint palliative and respiratory clinic to determine access to specialist palliative care and the initiation of NIV in MND patients. Methodology: The joint palliative care and respiratory clinic began in September 2015, at Musgrove Park hospital, Taunton and all patients with MND were included. Electronic records were retrospectively accessed, both from the acute hospital electronic document system (EPRO) and also the palliative care database (Crosscare). The joint clinic group were compared with patients discussed in the local MND multi-disciplinary team meeting prior to initiation of the joint clinic, who had respiratory symptoms (standard care group). Results: Data was collected in 35 patients with MND. Of these, 9 did not have any respiratory symptoms and were excluded. The joint clinic group (N = 11), included 5 women (45%), mean age 67.9 (SD 8.9); in the standard care group (N = 15) there were 7 (47%) women, mean age 69.2 (7.6) years. Eighty percent of patients receiving standard care were referred to palliative care compared to 100% in the joint clinic. In the standard care group, 12 (80%) of patients were initiated on NIV compared to 5 (45%) in the joint clinic group. There were only 3 unplanned admissions in both groups and the location of patient deaths were not different. Conclusion: Attending the joint clinic appeared to improve access to palliative care services. Furthermore, patients with MND may benefit from combined palliative and respiratory care input in a joint clinic when making decisions around the initiation of NIV. Further work is needed to evaluate the role of these clinics in informing patient choice for the management of ventilatory failure in this condition. Reference: National Institute for Health and Care Excellence. Motor Neurone Disease: assessment and management. https://www.nice.org.uk/guidance/ng42?unlid=3630474112016629201321 (accessed July 2016).